1981
DOI: 10.1152/ajpcell.1981.241.1.c68
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional flux ratio for potassium ions in depolarized frog skeletal muscle

Abstract: Small bundles of frog skeletal muscle fibers were loaded with 305 mM K+ and 120 mM Cl-, and 42K+ tracer efflux and influx were measured as a function of external K+ concentration ([K+]o) at a resting potential of -2 mV. As [K+]o was lowered from 305 mM, efflux decreased along a markedly sigmoidal curve, reaching a constant nonzero value at low [K+]o. Influx varied linearly with [K+]o at low [K+]o and more steeply at higher [K+]o. The ratio of influx to efflux was described by the equation: influx/efflux = exp[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…The flux-ratio exponent for these channels had a weak voltage dependence and attained a value as large as 3.3 at -40 mV. Horowicz et al (1968) and Spalding et al (1981) studied K + fluxes through inward rectifier K channels in skeletal muscle. They found that the flux-ratio exponent was near 1.0 at low external K concentrations and increased to 2 for high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The flux-ratio exponent for these channels had a weak voltage dependence and attained a value as large as 3.3 at -40 mV. Horowicz et al (1968) and Spalding et al (1981) studied K + fluxes through inward rectifier K channels in skeletal muscle. They found that the flux-ratio exponent was near 1.0 at low external K concentrations and increased to 2 for high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…inward rectifier (Adrian, 1962;Horowicz, Gage, and Eisenberg, 1968;Spalding, Senyk, Swift, and Horowicz, 1981), resulting in a crossover of outward currents (Noble and Tsien, 1968;Adrian, 1969). Crossover of the I-V relations are also evident for single channel currents measured at varying pipette K concentrations for inward rectifier channels of MDCK cells (Friedrich, Weiss, Paulmichl, and Lang, 1989) and basolateral membrane of rabbit proximal tubule cells (Parent, Cardinal, and Sauv~, 1988).…”
Section: K Currentsmentioning
confidence: 98%
“…Unidirectional tracer K + efflux decreases as [K+]o is decreased at a constant depolarized V~; when [K+]o = 0, K + efflux is at least one order of magnitude less than its maximum in high [K+]o (Adrian, 1962;Horowicz, Gage & Eisenberg, 1968;Spalding, Senyk, Swift & Horowicz, 1981). In addition, starting in K+-free solutions at constant V~, addition of external Rb + or external K + increases K + efflux (Adrian, 1962;Spalding, Swift, Senyk, and Horowicz, 1982).…”
Section: O/[k+]i) Both At Physiological V and [K+]o And At Depolarmentioning
confidence: 99%
“…In addition, starting in K+-free solutions at constant V~, addition of external Rb + or external K + increases K + efflux (Adrian, 1962;Spalding, Swift, Senyk, and Horowicz, 1982). For low concentrations of K + or Rb + the increment of K + efflux is proportional to the second power of either [K+]o or [Rb+]o and the proportionality constant depends on V~ (Spalding et al, 1981;. The conclusion from these studies is that the K + inward rectifier channel is activated from a state of low flux to a state of high flux when at least two sites within the membrane associated with the channel are occupied by K + coming from the external solution.…”
Section: O/[k+]i) Both At Physiological V and [K+]o And At Depolarmentioning
confidence: 99%
See 1 more Smart Citation